Transmission x-ray microscopy and its applications in battery material research—a short review. (13th August 2021) - Spence, Stephanie; Lee, Wah-Keat; Lin, Feng; Xiao, Xianghui
Abstract: Transmission x-ray microscopy (TXM), which can provide morphological and chemical structural information inside of battery component materials at tens of nanometer scale, has become a powerful tool in battery research. This article presents a short review of the TXM, including its instrumentation, battery research applications, and the practical sample preparation and data analysis in the TXM applications. A brief discussion on the challenges and opportunities in the TXM applications is presented at the end.